Approaches to delivering appropriate care to engage and meet the complex needs of refugee and asylum seekers in Australian primary healthcare: A qualitative study. (13th October 2022) - Patel, Pinika; Muscat, Danielle Marie; Bernays, Sarah; Zachariah, Dipti; Trevena, Emerita Lyndal
Abstract: This study aimed to provide insight and learnings from Australian general practitioners in facilitating positive interactions with refugee and asylum seeker patients and the role they play in helping those community members engage with healthcare. We conducted semi‐structured individual remote interviews with 12 general practitioners (GPs) who worked in areas with high refugee and migrant populations. Interview transcripts were coded inductively and deductively, based on the research questions, using Thematic Analysis. Extensive debriefing and discussion took place within the research team throughout data collection and analysis. Creating a culturally safe environment was an initial step taken by GPs to minimise the inherent power imbalance, in addition to applying the principles of trauma‐informed care (TIC) to appropriately listen and respond to their patients' needs and individual social circumstances. GPs at times were involved in using their role to advocate on behalf of their patient and played a key role in helping build their patients' health systems literacy. This study highlights the important role that GPs play in advocating and engaging refugee and asylum seeker patients, as well as helping them navigate the healthcare system. Whilst GPs practice can be made more efficient through experience and time; to deliver the care required GPs need to provide care in response to the individual's capacity and social circumstances. Enabling time and the application of the principles of TIC and cultural safety may allow for GPs to provide the quality of care that is needed in supporting patients from refugee and asylum seeker backgrounds.